Tailored Surgical Approaches for Foramem Magnum Tumors - Lynch, Jose Carlos; Pereira, Celestino Esteves; Weling, Leonardo C.; Gonçalves, Mariangela (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Objective To describe our surgical techniques, analyze their safety and their postoperative outcomes for foramen magnum tumors (FMTs).Methods From 1986 to 2014, 34 patients with FMTs underwent surgeries using either the lateral suboccipital approach, standard midline suboccipital craniotomy, or the far lateral approach, depending on the anatomic location of the lesions.Results In the present series, there were 22 (64.7%) female and 12 (35.2%) male patients. The age of the patients ranged from 12 to 63 years old. We observed 1 operative mortality (2.9%). A total of 28 patients (82.3%) achieved a score of 4 or 5 in the Glasgow Outcome Scale (GOS). Gross total resection (GTR) was obtained in 22 (64.7%) patients. After the surgery, 9 (26%) patients developed lower cranial nerve dysfunction (LCNd) weakness. The follow-up varied from 1 to 24 years (mean: 13.2 years).Conclusion The majority of tumors located in the FM can be safely and efficiently removed using either the lateral sub occipital approach, standard middle line sub occipital craniotomy, or the far lateral approach, depending on the anatomic location of the lesions.
Keywords: foramen magnum; foramen magnum meningiomas; foramen magnum tumors; microsurgery; retrocondylar approach; suboccipital approach